Analisis Penerapan Konsep Desain Arsitektur Tropis pada Hotel Alila Seminyak, Bali - Ni Putu Suda Nurjani (ATRIUM: Jurnal Arsitektur, 2023)
Title: Implementation’s Analysis of Tropical Architectural Design Concepts at Alila Seminyak Hotel, Bali   Tropical architecture is born from efforts to adjust to the climate in the tropics. Tropical architectural design always shows the form of adaptation of buildings to the environment. Traditional Balinese houses that function as community residential units are one of the tropical architectural typologies with the main advantage of thermal comfort, especially on air circulation flow that flows well throughout the building. However, when reviewing further commercial buildings in Bali, especially star hotels, the implementation of tropical architecture is a theme that requires deep design thinking. Adjustment to Balinese regional regulations on buildings is very binding; limited sites and demands for comfort and suitability of building functions are challenging for architects to design an accommodation building with a tropical architectural concept. Alila Seminyak Hotel is one of the five-star hotels outside the ITDC Nusa Dua area, which tries to form a tropical architectural identity as the main attraction. This qualitative descriptive research takes the case study of Alila Seminyak Hotel. Assessment analysis was carried out on the physical form of the hotel building, which was then appropriated and compared with tropical architectural theory. The results of this study show that the implementation of tropical architecture in the Alila Seminyak hotel building can be classified into several main elements, namely, first is the form of laying the building period on-site, second is the orientation pattern of the building, and third is The physical design of the building emphasizes, that this building have three main concept designs, it is namely insulation, shading, and cross ventilation.